Heimat in der Globalisierung - Heimat in der Schweiz - Barkhoff, Juergen (My University, 2019)
Taking Max Frisch’s speech Was ist Heimat? as a starting point, this contribution investigates in a first more general part, how our understanding of Heimat changes under the conditions of globalisation. Drawing on recent work especially on the cultural effects of globalisation, it asks in particular how the relationship between place, territory and cultural identity is affected and how this in turn affects the concept of Heimat, as it is so closely linked to notions of place and belonging. In doing so it looks also at the important nostalgic and imaginary components of Heimat. It then asks how an active concept of Heimat could look like that would overcome its inherent mechanisms of othering and exclusion and would be more comaptible with models of hybrid identities. This would be a concept of Heimat more adaptable to the challenges of globalisation than the historic ones with their strong emphasis on continuity, homgeneity and settledness. In a second part these ideas are tested and concretised by looking at texts from two very different Swiss authors. Thomas Hürlimann’s essayistic reflections about the changes globalisation has brought upon his hometown Zug articulate an insightful and sharp critique of globalisation, which observes the loss of Heimat on the temporal axis of a lived life. In doing so Hürlimann relates in a convincing way economic, societal and cultural processes. Melinda Nadj Abonji’s autobiographical novel Tauben fliegen auf negotiates difficult and painful processes of loosing once Heimat and of actively working to gaining a new one under the conditions of increased mobility and migration. It is doing so by tracing the transitory movements of its first-person narrator and protagonist between her original Serbian Heimat in the Vojvodina and the Zurich of the so called goldcoast and by reflecting on them.
PUBLISHED
Keywords: Place; Belonging; Globalisation; Switzerland; Identity; Literature of migration; Identities in Transformation